Remindly: Android-Based Task Reminder App with Agile Methods to Improve Student Study Time Efficiency - Artika Sari Dewi; Zahwa Aurellia Adha Maulana Syach; Anggun Nurpadila (Journal of Digital Technology and Computer Science, 2024)
The rapid development of digital technology demands practical solutions in time management, especially for students and students who often face difficulties in managing academic assignments. This research aims to develop the Remindly application, an Android-based task reminder application designed using the Agile method to help users systematically record, manage, and receive task notifications. The development process is carried out in three sprints, including the stages of planning, needs analysis, interface design, implementation, and testing. The app's key features include login, registration, task addition, automatic reminders, grouping tasks by status, and user profile management. The app was tested using both black-box and white-box methods, which showed that all functionality was running as planned. The Remindly application is expected to be able to improve the time efficiency, discipline, and productivity of users in daily activities, especially in the academic context.